2016
DOI: 10.1590/1413-812320152111.15562015
|View full text |Cite
|
Sign up to set email alerts
|

Autopercepção da saúde em idosos institucionalizados

Abstract: This study aimed to verify health self-perception, its prevalence and associated factors in institutionalized elderly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
3
32

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 14 publications
3
21
3
32
Order By: Relevance
“…As expected, age was strongly associated with poor self--perceived health both in the univariate and multivariate analyses. This was in line with a significant number of other studies, although some studies showed no association between age and self-perceived health or even the opposite effect of the age (Bonner et al, 2017;Menec & Nowicki, 2014;Jerez--Roig et al, 2016;Janković & Simić, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…As expected, age was strongly associated with poor self--perceived health both in the univariate and multivariate analyses. This was in line with a significant number of other studies, although some studies showed no association between age and self-perceived health or even the opposite effect of the age (Bonner et al, 2017;Menec & Nowicki, 2014;Jerez--Roig et al, 2016;Janković & Simić, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…In previous Brazilian studies, 35% of the institutionalized patients considered their health poor or very poor, 15 a high percentage when compared to the sample of this study, in which 15.8% consider their health poor or very poor. Studies from other countries have reported poor or very poor self-perceived health status among institutionalized older people from 15 to 63%.…”
Section: Discussioncontrasting
confidence: 52%
“…At the same time, literature reveals that being elderly is associated with a loss of functional capacity in a natural, gradual and progressive manner, with this process intensified by the presence of diseases and other situations. The profile resulting from limitations and coerced partial or total dependence in the performance of basic or instrumental activities of daily living influences the individual's perception of their own health, and is comprised of a vast group of aspects important for quality of life, many of which remain unknown and which can precede profiles of functional weakness 3,5,6 .…”
Section: Introductionmentioning
confidence: 99%